Safety assessment of the process Kunststof Recycling Nederland (KRN), used to recycle high density polyethylene box pallets for use as food contact materials. (10th June 2022) - ,; Lambré, Claude; Barat Baviera, José Manuel; Bolognesi, Claudia; Chesson, Andrew; Cocconcelli, Pier Sandro; Crebelli, Riccardo; Gott, David Michael; Grob, Konrad; Mengelers, Marcel; Mortensen, Alicja; Rivière, Gilles; et al.
Abstract: The EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP) assessed the safety of the recycling process Kunststof Recycling Nederland (KRN) (EU register number RECYC251). The input consists of box pallets made of high‐density polyethylene (HDPE) originating from a closed and controlled product loop for packaging of meat. Flakes are used to produce new box pallets for food contact. The Panel considered that the management system put in place to provide full traceability from the input to the final product and to ensure compliance of the origin of the input with Commission Regulation (EC) No 282/2008 is critical. According to the applicant, the input of the process KRN originates from a product loop which is in closed and controlled chain, designed to ensure that only materials and articles that have been intended for food contact are used and that contamination can be ruled out when run under the conditions described by the applicant. The Panel concluded that the recycling process KRN is suitable to produce recycled HDPE box pallets intended to be used in contact with refrigerated or frozen, packed or unpacked meat.